Amplified centrosomes in dendritic cells promote immune cell effector functions - Hauschild, Robert

Leveraging 2D data to learn textured 3D mesh generation - Henderson, Paul M; Tsiminaki, Vagia; Lampert, Christoph (Proceedings of the IEEE/CVF Conference on Computer Vision and Pattern Recognition)
Numerous methods have been proposed for probabilistic generative modelling of 3D objects. However, none of these is able to produce textured objects, which renders them of limited use for practical tasks. In this work, we present the first generative model of textured 3D meshes. Training such a model would traditionally require a large dataset of textured meshes, but unfortunately, existing datasets of meshes lack detailed textures. We instead propose a new training methodology that allows learning from collections of 2D images without any 3D information. To do so, we train our model to explain a distribution of images by modelling each image as a 3D foreground object placed in front of a 2D background. Thus, it learns to generate meshes that when rendered, produce images similar to those in its training set. A well-known problem when generating meshes with deep networks is the emergence of self-intersections, which are problematic for many use-cases. As a second contribution we therefore introduce a new generation process for 3D meshes that guarantees no self-intersections arise, based on the physical intuition that faces should push one another out of the way as they move. We conduct extensive experiments on our approach, reporting quantitative and qualitative results on both synthetic data and natural images. These show our method successfully learns to generate plausible and diverse textured 3D samples for five challenging object classes.

Unsupervised object-centric video generation and decomposition in 3D - Henderson, Paul M; Lampert, Christoph (34th Conference on Neural Information Processing Systems)
A natural approach to generative modeling of videos is to represent them as a composition of moving objects. Recent works model a set of 2D sprites over a slowly-varying background, but without considering the underlying 3D scene that gives rise to them. We instead propose to model a video as the view seen while moving through a scene with multiple 3D objects and a 3D background. Our model is trained from monocular videos without any supervision, yet learns to generate coherent 3D scenes containing several moving objects. We conduct detailed experiments on two datasets, going beyond the visual complexity supported by state-of-the-art generative approaches. We evaluate our method on depth-prediction and 3D object detection---tasks which cannot be addressed by those earlier works---and show it out-performs them even on 2D instance segmentation and tracking.

Phosphorous incorporation in Pd2Sn alloys for electrocatalytic ethanol oxidation - Yu, Xiaoting; Liu, Junfeng; Li, Junshan; Luo, Zhishan; Zuo, Yong; Xing, Congcong; Llorca, Jordi; Nasiou, Déspina; Arbiol, Jordi; Pan, Kai; Kleinhanns, Tobias; Xie, Ying; et al. (Nano Energy)
Direct ethanol fuel cells (DEFCs) show a huge potential to power future electric vehicles and portable electronics, but their deployment is currently limited by the unavailability of proper electrocatalysis for the ethanol oxidation reaction (EOR). In this work, we engineer a new electrocatalyst by incorporating phosphorous into a palladium-tin alloy and demonstrate a significant performance improvement toward EOR. We first detail a synthetic method to produce Pd2Sn:P nanocrystals that incorporate 35% of phosphorus. These nanoparticles are supported on carbon black and tested for EOR. Pd2Sn:P/C catalysts exhibit mass current densities up to 5.03 A mgPd−1, well above those of Pd2Sn/C, PdP2/C and Pd/C reference catalysts. Furthermore, a twofold lower Tafel slope and a much longer durability are revealed for the Pd2Sn:P/C catalyst compared with Pd/C. The performance improvement is rationalized with the aid of density functional theory (DFT) calculations considering different phosphorous chemical environments. Depending on its oxidation state, surface phosphorus introduces sites with low energy OH− adsorption and/or strongly influences the electronic structure of palladium and tin to facilitate the oxidation of the acetyl to acetic acid, which is considered the EOR rate limiting step. DFT calculations also points out that the durability improvement of Pd2Sn:P/C catalyst is associated to the promotion of OH adsorption that accelerates the oxidation of intermediate poisoning COads, reactivating the catalyst surface.

Memory tagging: Minimalist synchronization for scalable concurrent data structures - Alistarh, Dan-Adrian; Brown, Trevor A; Singhal, Nandini (Annual ACM Symposium on Parallelism in Algorithms and Architectures)
There has been a significant amount of research on hardware and software support for efficient concurrent data structures; yet, the question of how to build correct, simple, and scalable data structures has not yet been definitively settled. In this paper, we revisit this question from a minimalist perspective, and ask: what is the smallest amount of synchronization required for correct and efficient concurrent search data structures, and how could this minimal synchronization support be provided in hardware? To address these questions, we introduce memory tagging, a simple hardware mechanism which enables the programmer to "tag" a dynamic set of memory locations, at cache-line granularity, and later validate whether the memory has been concurrently modified, with the possibility of updating one of the underlying locations atomically if validation succeeds. We provide several examples showing that this mechanism can enable fast and arguably simple concurrent data structure designs, such as lists, binary search trees, balanced search trees, range queries, and Software Transactional Memory (STM) implementations. We provide an implementation of memory tags in the Graphite multi-core simulator, showing that the mechanism can be implemented entirely at the level of L1 cache, and that it can enable non-trivial speedups versus existing implementations of the above data structures.

Multiple-environment Markov decision processes: Efficient analysis and applications - Chatterjee, Krishnendu; Chmelik, Martin; Karkhanis, Deep; Novotný, Petr; Royer, Amélie (Proceedings of the 30th International Conference on Automated Planning and Scheduling)
Multiple-environment Markov decision processes (MEMDPs) are MDPs equipped with not one, but multiple probabilistic transition functions, which represent the various possible unknown environments. While the previous research on MEMDPs focused on theoretical properties for long-run average payoff, we study them with discounted-sum payoff and focus on their practical advantages and applications. MEMDPs can be viewed as a special case of Partially observable and Mixed observability MDPs: the state of the system is perfectly observable, but not the environment. We show that the specific structure of MEMDPs allows for more efficient algorithmic analysis, in particular for faster belief updates. We demonstrate the applicability of MEMDPs in several domains. In particular, we formalize the sequential decision-making approach to contextual recommendation systems as MEMDPs and substantially improve over the previous MDP approach.

An SMT theory of fixed-point arithmetic - Baranowski, Marek; He, Shaobo; Lechner, Mathias; Nguyen, Thanh Son; Rakamarić, Zvonimir (Automated Reasoning)
Fixed-point arithmetic is a popular alternative to floating-point arithmetic on embedded systems. Existing work on the verification of fixed-point programs relies on custom formalizations of fixed-point arithmetic, which makes it hard to compare the described techniques or reuse the implementations. In this paper, we address this issue by proposing and formalizing an SMT theory of fixed-point arithmetic. We present an intuitive yet comprehensive syntax of the fixed-point theory, and provide formal semantics for it based on rational arithmetic. We also describe two decision procedures for this theory: one based on the theory of bit-vectors and the other on the theory of reals. We implement the two decision procedures, and evaluate our implementations using existing mature SMT solvers on a benchmark suite we created. Finally, we perform a case study of using the theory we propose to verify properties of quantized neural networks.

Refinement for structured concurrent programs - Kragl, Bernhard; Qadeer, Shaz; Henzinger, Thomas A (Computer Aided Verification)
This paper presents a foundation for refining concurrent programs with structured control flow. The verification problem is decomposed into subproblems that aid interactive program development, proof reuse, and automation. The formalization in this paper is the basis of a new design and implementation of the Civl verifier.

Exponentially long lifetime of universal quasi-steady states in topological Floquet pumps - Gulden, Tobias; Berg, Erez; Rudner, Mark Spencer; Lindner, Netanel (SciPost Physics)
We investigate a mechanism to transiently stabilize topological phenomena in long-lived quasi-steady states of isolated quantum many-body systems driven at low frequencies. We obtain an analytical bound for the lifetime of the quasi-steady states which is exponentially large in the inverse driving frequency. Within this lifetime, the quasi-steady state is characterized by maximum entropy subject to the constraint of fixed number of particles in the system's Floquet-Bloch bands. In such a state, all the non-universal properties of these bands are washed out, hence only the topological properties persist.

Zero field splitting of heavy-hole states in quantum dots - Katsaros, Georgios; Kukucka, Josip; Vukušić, Lada; Watzinger, Hannes; Gao, Fei; Wang, Ting; Zhang, Jian-Jun; Held, Karsten (Nano Letters)
Using inelastic cotunneling spectroscopy we observe a zero field splitting within the spin triplet manifold of Ge hut wire quantum dots. The states with spin ±1 in the confinement direction are energetically favored by up to 55 μeV compared to the spin 0 triplet state because of the strong spin–orbit coupling. The reported effect should be observable in a broad class of strongly confined hole quantum-dot systems and might need to be considered when operating hole spin qubits.

Stem cell lineage survival as a noisy competition for niche access - Corominas-Murtra, Bernat; Scheele, Colinda L.G.J.; Kishi, Kasumi; Ellenbroek, Saskia I.J.; Simons, Benjamin D.; Van Rheenen, Jacco; Hannezo, Edouard B (Proceedings of the National Academy of Sciences of the United States of America)
Understanding to what extent stem cell potential is a cell-intrinsic property or an emergent behavior coming from global tissue dynamics and geometry is a key outstanding question of systems and stem cell biology. Here, we propose a theory of stem cell dynamics as a stochastic competition for access to a spatially localized niche, giving rise to a stochastic conveyor-belt model. Cell divisions produce a steady cellular stream which advects cells away from the niche, while random rearrangements enable cells away from the niche to be favorably repositioned. Importantly, even when assuming that all cells in a tissue are molecularly equivalent, we predict a common (“universal”) functional dependence of the long-term clonal survival probability on distance from the niche, as well as the emergence of a well-defined number of functional stem cells, dependent only on the rate of random movements vs. mitosis-driven advection. We test the predictions of this theory on datasets of pubertal mammary gland tips and embryonic kidney tips, as well as homeostatic intestinal crypts. Importantly, we find good agreement for the predicted functional dependency of the competition as a function of position, and thus functional stem cell number in each organ. This argues for a key role of positional fluctuations in dictating stem cell number and dynamics, and we discuss the applicability of this theory to other settings.

Filling the antibody pipeline in allergy: PIPE cloning of IgE, IgG1 and IgG4 against the major birch pollen allergen Bet v 1 - Köhler, Verena K.; Crescioli, Silvia; Fazekas-Singer, Judit; Bax, Heather J.; Hofer, Gerhard; Pranger, Christina L.; Hufnagl, Karin; Bianchini, Rodolfo; Flicker, Sabine; Keller, Walter; Karagiannis, Sophia N.; Jensen-Jarolim, Erika (International Journal of Molecular Sciences)
Birch pollen allergy is among the most prevalent pollen allergies in Northern and Central Europe. This IgE-mediated disease can be treated with allergen immunotherapy (AIT), which typically gives rise to IgG antibodies inducing tolerance. Although the main mechanisms of allergen immunotherapy (AIT) are known, questions regarding possible Fc-mediated effects of IgG antibodies remain unanswered. This can mainly be attributed to the unavailability of appropriate tools, i.e., well-characterised recombinant antibodies (rAbs). We hereby aimed at providing human rAbs of several classes for mechanistic studies and as possible candidates for passive immunotherapy. We engineered IgE, IgG1, and IgG4 sharing the same variable region against the major birch pollen allergen Bet v 1 using Polymerase Incomplete Primer Extension (PIPE) cloning. We tested IgE functionality and IgG blocking capabilities using appropriate model cell lines. In vitro studies showed IgE engagement with FcεRI and CD23 and Bet v 1-dependent degranulation. Overall, we hereby present fully functional, human IgE, IgG1, and IgG4 sharing the same variable region against Bet v 1 and showcase possible applications in first mechanistic studies. Furthermore, our IgG antibodies might be useful candidates for passive immunotherapy of birch pollen allergy.

Epinephrine drives human M2a allergic macrophages to a regulatory phenotype reducing mast cell degranulation in vitro - Gotovina, Jelena; Bianchini, Rodolfo; Fazekas-Singer, Judit; Herrmann, Ina; Pellizzari, Giulia; Haidl, Ian D.; Hufnagl, Karin; Karagiannis, Sophia N.; Marshall, Jean S.; Jensen‐Jarolim, Erika (Allergy)

Estimating inbreeding and its effects in a long-term study of snapdragons (Antirrhinum majus) - Arathoon, Louise S
Here are the research data underlying the publication "Estimating inbreeding and its effects in a long-term study of snapdragons (Antirrhinum majus)". Further information are summed up in the README document. The files for this record have been updated and are now found in the linked DOI https://doi.org/10.15479/AT:ISTA:9192.

Selective routing of spatial information flow from input to output in hippocampal granule cells - Zhang, Xiaomin; Schlögl, Alois; Jonas, Peter M (Neuron)
Dentate gyrus granule cells (GCs) connect the entorhinal cortex to the hippocampal CA3 region, but how they process spatial information remains enigmatic. To examine the role of GCs in spatial coding, we measured excitatory postsynaptic potentials (EPSPs) and action potentials (APs) in head-fixed mice running on a linear belt. Intracellular recording from morphologically identified GCs revealed that most cells were active, but activity level varied over a wide range. Whereas only ∼5% of GCs showed spatially tuned spiking, ∼50% received spatially tuned input. Thus, the GC population broadly encodes spatial information, but only a subset relays this information to the CA3 network. Fourier analysis indicated that GCs received conjunctive place-grid-like synaptic input, suggesting code conversion in single neurons. GC firing was correlated with dendritic complexity and intrinsic excitability, but not extrinsic excitatory input or dendritic cable properties. Thus, functional maturation may control input-output transformation and spatial code conversion.

Compressive sensing using iterative hard thresholding with low precision data representation: Theory and applications - Gurel, Nezihe Merve; Kara, Kaan; Stojanov, Alen; Smith, Tyler; Lemmin, Thomas; Alistarh, Dan-Adrian; Puschel, Markus; Zhang, Ce (IEEE Transactions on Signal Processing)
Modern scientific instruments produce vast amounts of data, which can overwhelm the processing ability of computer systems. Lossy compression of data is an intriguing solution, but comes with its own drawbacks, such as potential signal loss, and the need for careful optimization of the compression ratio. In this work, we focus on a setting where this problem is especially acute: compressive sensing frameworks for interferometry and medical imaging. We ask the following question: can the precision of the data representation be lowered for all inputs, with recovery guarantees and practical performance Our first contribution is a theoretical analysis of the normalized Iterative Hard Thresholding (IHT) algorithm when all input data, meaning both the measurement matrix and the observation vector are quantized aggressively. We present a variant of low precision normalized IHT that, under mild conditions, can still provide recovery guarantees. The second contribution is the application of our quantization framework to radio astronomy and magnetic resonance imaging. We show that lowering the precision of the data can significantly accelerate image recovery. We evaluate our approach on telescope data and samples of brain images using CPU and FPGA implementations achieving up to a 9x speedup with negligible loss of recovery quality.

Origin of a subgenome and genome evolution of allotetraploid cotton species - He, Peng; Zhang, Yuzhou; Xiao, Guanghui (Molecular Plant)

Stochastic games with lexicographic reachability-safety objectives - Chatterjee, Krishnendu; Katoen, Joost P; Weininger, Maximilian; Winkler, Tobias (International Conference on Computer Aided Verification)
We study turn-based stochastic zero-sum games with lexicographic preferences over reachability and safety objectives. Stochastic games are standard models in control, verification, and synthesis of stochastic reactive systems that exhibit both randomness as well as angelic and demonic non-determinism. Lexicographic order allows to consider multiple objectives with a strict preference order over the satisfaction of the objectives. To the best of our knowledge, stochastic games with lexicographic objectives have not been studied before. We establish determinacy of such games and present strategy and computational complexity results. For strategy complexity, we show that lexicographically optimal strategies exist that are deterministic and memory is only required to remember the already satisfied and violated objectives. For a constant number of objectives, we show that the relevant decision problem is in NP∩coNP , matching the current known bound for single objectives; and in general the decision problem is PSPACE -hard and can be solved in NEXPTIME∩coNEXPTIME . We present an algorithm that computes the lexicographically optimal strategies via a reduction to computation of optimal strategies in a sequence of single-objectives games. We have implemented our algorithm and report experimental results on various case studies.

Structure and mechanism of the Mrp complex, an ancient cation/proton antiporter - Steiner, Julia; Sazanov, Leonid A (eLife)
Multiple resistance and pH adaptation (Mrp) antiporters are multi-subunit Na+ (or K+)/H+ exchangers representing an ancestor of many essential redox-driven proton pumps, such as respiratory complex I. The mechanism of coupling between ion or electron transfer and proton translocation in this large protein family is unknown. Here, we present the structure of the Mrp complex from Anoxybacillus flavithermus solved by cryo-EM at 3.0 Å resolution. It is a dimer of seven-subunit protomers with 50 trans-membrane helices each. Surface charge distribution within each monomer is remarkably asymmetric, revealing probable proton and sodium translocation pathways. On the basis of the structure we propose a mechanism where the coupling between sodium and proton translocation is facilitated by a series of electrostatic interactions between a cation and key charged residues. This mechanism is likely to be applicable to the entire family of redox proton pumps, where electron transfer to substrates replaces cation movements.

Free space Ramsey spectroscopy in rubidium with noise below the quantum projection limit - Malia, Benjamin K.; Martínez-Rincón, Julián; Wu, Yunfan; Hosten, Onur; Kasevich, Mark A. (Physical Review Letters)
We demonstrate the utility of optical cavity generated spin-squeezed states in free space atomic fountain clocks in ensembles of 390 000 87Rb atoms. Fluorescence imaging, correlated to an initial quantum nondemolition measurement, is used for population spectroscopy after the atoms are released from a confining lattice. For a free fall time of 4 milliseconds, we resolve a single-shot phase sensitivity of 814(61) microradians, which is 5.8(0.6) decibels (dB) below the quantum projection limit. We observe that this squeezing is preserved as the cloud expands to a roughly 200  μm radius and falls roughly 300  μm in free space. Ramsey spectroscopy with 240 000 atoms at a 3.6 ms Ramsey time results in a single-shot fractional frequency stability of 8.4(0.2)×10−12, 3.8(0.2) dB below the quantum projection limit. The sensitivity and stability are limited by the technical noise in the fluorescence detection protocol and the microwave system, respectively.